Estimation of myocardial infarct size in man using 99m Tc polyphosphate. Issue 6 (June 1979) - Davies, G J; Fakhrai, B; Morgan, A; Muir, J R
Abstract : We have critically evaluated the use of 99m Tc polyphosphate to estimate myocardial infarct size. Optimum conditions were first defined with respect to infarct edge definition, and relative activity over infarct and bone and in blood pool. The scintigrams of 53 patients with acute transmural myocardial infarction were recorded under these defined constant conditions and analysed in various ways. Visual grading of infarct area or intensity correlated poorly with other indices of infarct severity. Computer-assisted measurements of above-background infarct uptake area or of total farct activity correlated well with clinical, electrocardiographic, and enzymatic measurements of infarct severity.